Energy productivity, the new frontier for GCC countries - Alsuraih, W (Oxford Institute for Energy Studies, 2015)
The recent decline in oil price – the largest in terms of annual average when compared to those of 1986 and 2009 – turned the 2014 budget surplus for Gulf Cooperation Council (GCC) countries into a deficit of about 8 per cent of combined GDP in 2015, according to the International Monetary Fund (IMF). Since 2014, natural gas prices have also shown a declining trend, although not as pronounced as oil. In response, governments have dug into their reserves and are tapping new sources of financing, particularly government bonds. Global estimates show the oil price may remain depressed for the foreseeable future, implying slow recovery in the short to medium term.